Defining Quality Indicators for Best-Practice Management of Inflammatory Bowel Disease in Canada - Geoffrey C Nguyen; Shane M Devlin; Waqqas Afif; Brian Bressler; Steven E Gruchy; Gilaad G Kaplan; Liliana Oliveira; Sophie Plamondon; Cynthia H Seow; Chadwick Williams; Karen Wong; Brian M Yan; et al. (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: There is a paucity of published data regarding the quality of care of inflammatory bowel disease (IBD) in Canada. Clinical quality indicators are quantitative end points used to guide, monitor and improve the quality of patient care. In Canada, where universal health care can vary significantly among provinces, quality indicators can be used to identify potential gaps in the delivery of IBD care and standardize the approach to interprovincial management.